Woman, thou art loosed! : healing the wounds of the past - Jakes, T. D. (Tulsa, Okla. : Albury Pub., 1996)
With words that stand the test of time, T.D. Jakes' three books cross denominational lines, racial barriers, and gender biases to reach into the heart of the reader. With the compassion of Jesus Christ, he touches the hidden places of every woman's heart to bring healing to past wounds with the phenomenal best-selling Woman, Thou Art Loosed! With the same intensity he calls all men, women, and children to stop being afraid to reveal what God longs to heal in Naked and Not Ashamed. Only when we drop our masks and facades can we be real before our Lord and others. And with Can You Stand to Be Blessed? T.D. Jakes, a man of many accomplishments and life goals, shares personal insights that will help all people survive the peaks and valleys of daily living out God's call upon their lives.
Keywords: Christian women -- Religious life; Spiritual healing; Christian women -- religious life; Christian women -- Religious life; Spiritual healing